2010
DOI: 10.1002/ar.21213
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgical Anatomy of Lumbosacral Nerve Rootlets for Highly Selective Rhizotomy in Chronic Spinal Cord Injury

Abstract: It is known that selective sacral roots rhizotomy is effective for relieving the neurogenic bladder associated with spinal cord injury. The goal of this study is to review the surgical anatomy of the lumbosacral nerve rootlets and to provide some morphological bases for highly selective sacral roots rhizotomy. Spinal cord dissections were performed on five cadavers under surgical microscope. At each spinal cord segment, we recorded the number, diameter and length of the rootlets, subbundles and bundles from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 19 publications
0
12
1
Order By: Relevance
“…In fact, the most frequent complications of DREZ surgery at the thoracic level are ipsilateral leg weakness and a likely reduction in bladder reflexes [14]. At each spinal segment, a few rootlets emerge to give rise to a dorsal root; the number of dorsal rootlets varies at each spinal cord segment [4,7,17,18]. Most thoracic segments give rise to 3-4 dorsal rootlets, which are fewer than those seen at the cervical and lumbosacral segments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the most frequent complications of DREZ surgery at the thoracic level are ipsilateral leg weakness and a likely reduction in bladder reflexes [14]. At each spinal segment, a few rootlets emerge to give rise to a dorsal root; the number of dorsal rootlets varies at each spinal cord segment [4,7,17,18]. Most thoracic segments give rise to 3-4 dorsal rootlets, which are fewer than those seen at the cervical and lumbosacral segments.…”
Section: Discussionmentioning
confidence: 99%
“…The dorsal rootlet entry into the posterolateral sulcus varies in accordance with the levels of the spinal cord. Although these relationships have been studied in detail for cervical, lumbar, and sacral spinal segments, such information is not available for thoracic segments [4,6,7,17,18]. Though less frequent, thoracic DREZ surgeries are performed in cases of postherpetic neuralgia, spasticity and/or pain after spinal cord injury, and pain due to malignant invasions of the thorax and abdominal wall [2,15].…”
Section: Introductionmentioning
confidence: 99%
“…Typically, a number of rootlets originate from the corresponding level of spinal cord, and then they are aggregated gradually to form nerve sub-bundles, bundles, and finally a nerve root. 7 As shown in Fig. 1 (Parts A, B, and C), the ventral roots adjacent to the dura usually consisted of only one nerve bundle while most dorsal roots normally comprised several nerve bundles.…”
Section: Histological Microstructure Of Spinal Nerve Rootsmentioning
confidence: 94%
“…[61516] Kirazli et al . found that the average number of dorsal thoracic rootlets is 6.6 ± 0.8, which is higher than what Sindou found.…”
Section: Resultsmentioning
confidence: 99%
“…[3334] However, others reports suggest that there is side-independence of the spinal dimensions. [163536] In terms of sexual dimorphism, Rühli et al . found that IVF width is greater in females than males.…”
Section: Discussionmentioning
confidence: 99%